2019
DOI: 10.21203/rs.2.16060/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imaging modality for measuring the presence and extent of the labral lesions of the shoulder: a systematic review and meta-analysis

Abstract: Background: Multiple published studies quantitatively analysing the diagnostic value of MRI, MR arthrography (MRA) and CT arthrography (CTA) for labral lesions of the shoulder have had inconsistent results. The aim of this meta-analysis was to systematically compare the diagnostic performance of MRI, MRA, CTA and CT. Methods: Two databases, PubMed and EMBASE, were used to retrieve studies targeting the accuracy of MRI, MRA, CTA and CT in detecting labral lesions of the shoulder. After carefully screening and e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Moreover, other research performed in our lab's con rmed that MRI had a similar sensitivity and speci city to MRA in the detection of bursal-sided PTRCTs [19]. In addition, another meta-analysis revealed that MRI is by far the rst choice recommendation for imaging modality for the detection of acute labral lesions [32]. Recently, one study in 2020 using hierarchical summary receiver operating characteristic curves (HSROC) demonstrated that MRI was recommended to be a rst-choice imaging modality for the detection of rotator cuff tears [38].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Moreover, other research performed in our lab's con rmed that MRI had a similar sensitivity and speci city to MRA in the detection of bursal-sided PTRCTs [19]. In addition, another meta-analysis revealed that MRI is by far the rst choice recommendation for imaging modality for the detection of acute labral lesions [32]. Recently, one study in 2020 using hierarchical summary receiver operating characteristic curves (HSROC) demonstrated that MRI was recommended to be a rst-choice imaging modality for the detection of rotator cuff tears [38].…”
Section: Discussionmentioning
confidence: 61%
“…A network meta-analysis of 144 diagnostic studies involving 14059 patients (14212 shoulders) demonstrated that for the detection of full-thickness tears, partial-thickness tears, or any tear, MRA had the highest sensitivity, speci city, and superiority index in three common-used imaging modalities (MRA, MRI and US), which revealed that high-eld MRA had the highest diagnostic value for detecting any tear, followed by low-eld MRA, high-eld MRI, high-frequency US, low-eld MRI, and low-frequency US [16]. In addition, another meta-analysis included 14 studies involving 1216 patients with labral lesions, revealed that MRA had the highest sensitivity and speci city compared with those of MRI and CTA, which indicated that MRA was suggested for use in patients with chronic shoulder symptoms or a pathologic abnormality [32]. MRA has a good diagnostic performance mainly depending on the objective evidence of the leakage of contrast agent, accompanied by a good anatomic resolution and subtle defects depicted by contrast agents [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…6 In addition, another meta-analysis of 14 studies involving 1216 patients with labral lesions revealed that MRA had the highest sensitivity and specificity compared with those of MRI and CTA, which indicated that MRA was suggested for use in patients with chronic shoulder symptoms or a pathological abnormality. 22 MRA has a good diagnostic performance mainly depending on the objective evidence of the leakage of contrast agent, accompanied by a good anatomic resolution and subtle defects depicted by contrast agents. 23,24 Nonetheless, MRA, as an invasive diagnosis modality, has many disadvantages and limitations, including a longer examination time, increased risk of infection and adverse complications.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, another meta-analysis revealed that MRI is by far the first choice recommendation for imaging modality for the detection of acute labral lesions. 22 Recently, one study in 2020 using hierarchical summary receiver operating characteristic curves (HSROC) demonstrated that MRI was recommended to be a firstchoice imaging modality for the detection of rotator cuff tears. 28 Although MRA has a higher sensitivity and specificity, it cannot replace MRI after the comprehensive consideration of accuracy and practicality.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the gold standard arthroscopy, the sensitivity of imaging techniques varies between 60 and 95% soft-tissue lesions while CTA shows sensitivity and specificity close to 100% for bony lesions. [6][7][8][9][10] Evidence regarding the prevalence of lesions is lacking. Systematic reviews determining the prevalence are limited and epidemiological studies show a varying range in the observed prevalence of lesions [11][12][13].…”
Section: Introductionmentioning
confidence: 99%